Bullying In Children: A Concept Analysis - Eni Hidayati; Andria Pragholapati; Suhartini Ismail (Journal of the Pakistan Medical Association, 2024)
Bullying can occur in various settings, including workplace, home, neighbourhood, playground and others. The framework for examining bullying in the current narrative employed 8 methodical processes for concept analysis, including selecting a concept, determining the analysis's goals or purpose, identifying all of the concept's applications, identifying its defining characteristics, developing additional cases, building a case model, identifying antecedents and consequences, and selecting empirical references. The current narrative review comprised search on ProQuest, PubMed and Scopus databases for relevant literature with the aim of improving understanding related to bullying, which is wrong as it hurts other people. Keywords: Goals, Bullying, Bibliometrics, Hurting, Forcing, Intimidating.